1991
DOI: 10.1007/bf00186877
|View full text |Cite
|
Sign up to set email alerts
|

A prospective review of arthroscopic debridement for degenerative joint disease of the knee

Abstract: A prospective review of 254 patients with moderate or severe knee pain due to degenerative joint disease, treated by arthroscopic debridement of menisci, articular cartilage, osteophytes and loose bodies has been made 24 to 140 months (average of 44 months) after surgery. Patients ranged in age from 28 to 82 years with an average of 49 years. At review, 75% had minimal discomfort and improved function and 85% were satisfied with the treatment. Those with less radiographic arthritis, less severe involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 16 publications
0
17
1
4
Order By: Relevance
“…Other authors have been more critical (Casscells 1990). All the previously reported trials of articular debridement have included many knees on which a partial meniscectomy had been performed at the same operation (Aichroth, Patel and Moyes 1991;Rand 1991;Chang et al 1993); the results of these could equally well be described as a review of meniscectomy with some articular debridement. As previously discussed, the use of the blanket term 'debridement' may cover many types of arthroscopic surgery and is almost impossible to quantify.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have been more critical (Casscells 1990). All the previously reported trials of articular debridement have included many knees on which a partial meniscectomy had been performed at the same operation (Aichroth, Patel and Moyes 1991;Rand 1991;Chang et al 1993); the results of these could equally well be described as a review of meniscectomy with some articular debridement. As previously discussed, the use of the blanket term 'debridement' may cover many types of arthroscopic surgery and is almost impossible to quantify.…”
Section: Resultsmentioning
confidence: 99%
“…1 Successful outcomes for articular cartilage lesions have been reported with current treatment options, which include joint lavage, tissue debridement, abrasion arthroplasty, microfracture of the subchondral bone, or the transplantation of autologous or allogeneic osteochondral grafts. [2][3][4][5][6][7][8][9][10][11][12][13] While these procedures have yielded promising clinical results, many of these approaches can lead to the formation of fibrous tissue, apoptosis, and further cartilage degeneration. [14][15][16] Currently, one tissue engineering approach, autologous chondrocyte implantation (ACI), has demonstrated positive results in early clinical reports, [17][18][19][20][21] but randomized controlled trials suggest similar efficacy of the ACI procedure compared to the microfracture technique or mosaicplasty.…”
mentioning
confidence: 99%
“…Although OA of the knee has a female predominance, only 3 of 16 studies listed in Table 5 included more women than men. Only two studies listed someone other than the operating surgeon as the primary assessor of outcome [48,57]. A clinician other the operating surgeon interviewed and examined all patients in the study of Aichroth et al Whether the evaluating clinician was blinded to the findings of surgery was not reported.…”
Section: Arthroscopic Debridementmentioning
confidence: 99%
“…Data from 16 case series reporting on arthroscopic debridement of OA are reviewed in Table 5 [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Good and excellent results, as defined by the respective authors, are reported in 40% to 75% of patients at final follow-up.…”
Section: Arthroscopic Debridementmentioning
confidence: 99%